O układzie alfabetycznym w dawnych słownikach przekładowych - Lenartowicz-Zagrodna, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2017)
Alphabetical order is one of the four ways to organize words in dictionaries. Throughout history it was changing — it was depending on the level of knowledge about the language and on the evolution of Polish lexicography. The major problem was the lack of Polish orthography, especially the notation of phons, which have no equivalents in Latin. The aim of the study is to investigate the evolution of the alphabetical system in the history of Polish lexicography and to indicate the problems faced by the authors from 16th to the 19th century.